Cyclic thermal storage/discharge performances of a hypereutectic Cu-Si alloy under vacuum for solar thermochemical process. (15th October 2016) - Gokon, Nobuyuki; Yamaguchi, Tomoya; Kodama, Tatsuya
Abstract: A copper-silicon alloy (Cu-Si alloy) was examined and evaluated as a phase-change material (PCM) for thermal energy storage applications such as load shaving and peak load shifting when coupled to a solar thermochemical reactor, reformer, or gasifier for the production of solar fuel. The Cu-Si alloy was selected as a high-temperature PCM thermal storage medium alternative to molten carbonate salts, and the compatibility of this alloy with a graphite-carbon encapsulation material was experimentally examined. The cyclic thermal storage/discharge properties of the Cu-Si alloy as a latent-heat energy storage material were studied with respect to thermal cycles. A thermal stability test was performed on Cu-20 wt% Si, Cu-25 wt% Si, and Cu-30 wt% Si alloys placed in a graphite container under vacuum. The performances of the Cu-Si alloys with increasing and decreasing temperature were measured during the thermal storage (heat-charge) and cooling (heat-discharge) modes, respectively. The elemental distribution of each Cu-Si alloy after the cyclic reaction was evaluated using an electron probe microanalyzer (EPMA). The heat storage capacities before and after the cyclic reaction were evaluated using differential scanning calorimetry (DSC) and were compared to the thermal storage properties of the molten carbonate salt. Highlights: A hypereutectic Cu-Si alloy is tested for a latent heat thermal storage. The temperature variations are examined during the heat charge/discharge modes. The heat storage capacity is compared with that of carbonate molten salts.